SKILL - BASED CREATION OF CLASS ROOM ENVIRONMENT - Borgaonkar, Jayant Shankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The process of living one’s life independently teaches one to lead his life based on skills develops a constructive approach between a teacher and students and thereby creates a fresh enthusiasm in the teaching - learning process and develops an interactive approach. Skill - based class room environment teaches one to lead his life successfully. From skill - based class climate, an atmosphere of self - awareness and self - confidence is induced and moral values are cultivated in students from which an all - round (a multi - faceted) citizen can be developed. Through it, knowledge - oriented and good natured students are moulded and an education system, based on skills can be developed and it becomes easy to present skill - based topics. Among students, interest in a topic (a subject) can be created and one can express one’s own thoughts in one’s own language. By strictly adhering to such virtues as the spirit of cooperation, goodness (good nature) and the ability to lead a group are created and an ideal attitude (approach) can be developed amongst students and a democratic society can be developed from self - dependent (independent) approach.